Unresolvable Tensions and Ethical Dilemmas: Reflections on the Experience of Doing “Prison Research” in China—A Research Note - Zhang, Shaoying (The prison journal, 2019)
In this article, I reflect on the ethical implications of my research visit to China’s prisons. I argue that satisfying instituted ethical protocols in this type of research is the beginning of the ethical process, not the end. “Ethical research” involves constant reflection on how the researcher’s self is constituted in relation to others, not only the primary research group but also fellow researchers, gatekeepers, facilitators, prison officials, and the representatives of the many organizations involved in such a program. Interpretive or critical inquiries are not solely about deciding “whose side we are on,” but more about what kind of relations between the self and various stakeholders existed before, during, and after fieldwork.